Nodular cutaneous metastasis of the leg in advanced urothelial bladder carcinoma: a case report and systematic literature review - Izzo, Paolo; Izzo, Luciano; Lai, Silvia; D’Onghia, Giuliano; Giancontieri, Paola; Gabriele, Raimondo; Polistena, Andrea; Sibio, Simone; Costanzo, Maria Ludovica; De Intinis, Claudia; Izzo, Sara (Frontiers in Oncology, 2023)
Cutaneous metastases from urothelial carcinoma (UC) are very rare and indicate advanced disease with poor prognosis. A 63-year-old female patient with a history of urothelial bladder carcinoma, treated two months prior with radical cystectomy and adjuvant gemcitabine and cisplatin (GC) therapy, presented a skin lesion localized in lower third of the right leg. Punch biopsy revealed carcinomatous metastasis which urothelial origin was confirmed by immunohistochemical analysis. 18-FDG PET-CT showed spread of metastases to the lung and left ischium. Our review focuses on the time between surgery and skin metastasis, the localization and the prognosis after metastasis diagnosis. In many cases, skin metastases occur within one year of initial UC surgery and in most cases occur on the abdominal wall. Local wide excision of metastasis should be considered in selected cases, however chemotherapy remain the main treatment.